ALTERNATIF MODEL TOKO BUKU ONLINE UNTUK UNIVERSITAS TERBUKA - Dwi A Aprijani; Tengku Eduard Azwar Sinar; Unggul Utan Sufandi; Kani Kani; Firmansyah Firmansyah (LPPM Universitas Terbuka, 2010)
The purpose of this research is to find an alternative model for Online bookstore that works for Universitas Terbuka. The alternative model should reduce the difference between the ordering and delivering transaction, which in turn can improve the performance of Toko Buku Online UT. Results showed that there were several significant factors that must be present in the Online bookstore system. Such factors are treating customers well by including updated information about orders that have been made; improving business processes continuously and periodically based on input and evaluation from the consumer; letting consumers decide their own transactions by providing FAQ (Frequently Asked Questions) facility; and performing personal services among others through email and chat facility. Based on these findings, the proposed recommendations is to add some features to the system of Toko Buku Online UT. These features include buffer stocks, auto-reply mechanism, information about the delivery and return of materials, chat facility (facebook, twitter, yahoo messenger), and FAQ facility.